PENGARUH KONSENTRASI PELARUT TERHADAP AKTIVITAS ANTIOKSIDAN SEDIAAN SERUM EKSTRAK KULIT BUAH NAGA MERAH (Hylocereus Polyrhizus) - Fatah, Muhammad Ilman; Muldiyana , Tya; Kusnadi , Kusnadi (JIFI (Jurnal Ilmiah Farmasi Imelda), 2024)
The skin of red dragon fruit (Hylocereus Polyrhizus) contains active substances that are useful for extracting in making natural serums. Antioxidants, one of the important compounds in serum that can protect the skin and capture free radicals. This study aims to prove the presence of antioxidants in serum made from red dragon fruit peel extract, and to compare the effect of using 70% and 96% ethanol solvents on the physical properties and antioxidant activity of the serum. The extraction method used was maceration extraction, by testing the flavonoid content and free ethanol content in the extract. The physical properties of the serum were tested including organoleptics, pH, homogeneity, viscosity, spreadability and stickiness. Meanwhile, antioxidant activity was tested using the UV-VIS spectrophotometric method. The research results show that red dragon fruit peel extract contains flavonoids with orange and red colors, and does not have an ester odor. Serum preparations from 70% and 96% ethanol extracts have semisolid form, characteristic odor, color differences, pH 5, homogeneous, with viscosities of 464 cPs and 341 cPs respectively. The spreadability of the serum is 7.1 cm and 9.7 cm, while the adhesive power is 0.88 and 0.93. The serum antioxidant activity of 70% and 96% ethanol extracts was 39.59 µg/mL and 45.87 µg/mL. The 70% ethanol extract serum meets the standard physical properties of serum and has stronger antioxidant activity compared to the 96% ethanol extract serum, indicated by the lower IC50 value. Flavonoids, as antioxidant compounds, have various types and different polarities depending on the position and number of hydroxyl groups.